La crítica al modelo Rawlsiano de Quentin Skinner - Bustamante Kuschel, Gonzalo (Conceptos Históricos, 2017)
Quentin Skinner’s project uses a form of analysis – both linguistic and contextual – that tries to show the ideological intentionalities of political thought. Skinner seeks to develop a history that is sufficiently attentive to his own politicization and that can show the context of political thought and account for the intentionality and ideological conflict through which all discourse and sociopolitical proposition arises. I propose that it is plausible to argue that Skinner’s methodology is inseparable from his intention to rescue Republicanism. This becomes evident in the structuring of his criticism of John Rawls. The author of A Theory of Justice is read by the British historian – in line with Hobbes– as another moment of political neutralization of theory. In the following, I will present the main aspects of Skinner’s criticism of Rawlsian liberalism, and discuss in how far these criticisms are or are not conclusive with regard to the relationship between Rawls and Republicanism. Finally, I will assess in how far there is an ideological intentionality in the British historian which would put his methodology in line with the same characteristics of Republicanism.